(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Pleural empyema has got a very old history which dates back to the times of Hippocrates. The modern era of broad spectrum antibiotics has reduced the threat in developed countries but the danger persists in developing world. Early surgical intervention is what is recommended in great majority of cases. Closed aspiration / fibrinolysis, Tube Thoracostomy, Video Assisted Thoracoscopic Decortication and Open Lung Decortication are the measures in practice for the last many years. Open Lung Decortication (OLD) has been thought to be the most successful modality but its longer incision reserved its use in specific cases only. Limited Thoracotomy and Video Assisted Thoracoscopic Decortication however, have encouraged use of aggressive modalities in cases of Empyema. Material & Methods: From 1st July 2011-31st December 2011, 152 OLD (open lung decortications) were done using limited thoracotomy and collected data will be presented in the study. Informed consent taken from all patients and only those were included who opted for thoracotomy. Results: Out of these152 patients, 82 were male and 70 females. Larger number of patients belonged to age group 20-30 yrs (55).The results were judged on specified criteria. The approach was quite successful in 129 patients and satisfactory results obtained. Improvement was judged on clinical and radiological basis and patients were followed up for 1 year In 23 patients the approach did not succeed as incision had to be extended. All these patients however had a fibro thorax and the history of empyema was more than 8 weeks in all these cases. The hospital stay was < 2 weeks in nearly 70 % patients. There was very little morbidity and no mortality. Conclusion: We conclude that OLD with muscle sparing limited thoracotomy has unlimited benefits and should be considered in all 2nd and 3rd stage empyema cases.